COMPARING TWO MODES OF PRESENTATION ON PERCEPTIONS OF FLU THREAT AND ATTRIBUTIONS FOR ITS GLOBAL OUTBREAK - C.H. WONG, Norman; A. HARVELL, Lindsey; ANAZ, Necati (European Journal of Geography, 2023)
This study compared the effects of presenting the H1N1 flu threat using two different modes of presentation: via an interactive map (visual mode) versus using words and numbers (numerical mode) on people’s threat perceptions (susceptibility and severity) regarding the H1N1 flu, attributions for the rapid spread of the H1N1 virus, and intentions to seek additional information about the H1N1 flu in the next 6 months. Three hundred eighteen undergraduate students were recruited to take part in this experiment. Results found that compared to those exposed to a numerical representation of the H1N1 flu threat, or receiving a control message, those exposed to a visual representation of the threat reported greater feelings of H1N1 flu susceptibility and held stronger immigration-related attributions for the spread of the virus. Also, the visual representation of the H1N1 flu threat reinforced the negative attitudes among those who already held aversive attitudes toward Mexicans, as reflected in stronger immigrant-related attributions for the spread of the virus. Implications of the results for designing messages involving outbreaks of communicable diseases (such as the H1N1 virus) are discussed.